Can isepamicin be a potential option for extended spectrum beta-lactamases and carbapenemases expressing Escherichia coli? - Yamuna Devi Bakthavatchalam; Fiza Abdullah; Devishree Srinivasan; Ayyanraj Neeravi; Rani Diana Sahni; Abi Manesh; Balaji Veeraraghavan (Elsevier, 2024)
Background: Beta-lactamase expressing Enterobacterales are challenging to treat. The potency of aminoglycosides as a bactericidal agent has increased interest in using them in combination regimens. In the present study, we evaluated the in-vitro activity of isepamicin and its comparator against phenotypically confirmed ESBL and carbapenemase expressing E. coli isolates. Methods: ESBL-E. coli (n = 103) and carbapenemase expressing E. coli (n = 105) collected from various clinical samples were included in this study. The minimum inhibitory concentrations (MICs) of ceftazidime, meropenem, gentamicin, amikacin, and isepamicin were determined using the broth microdilution method according to CLSI guidelines. Results: Isepamicin potently inhibited 98% of ESBL expressing E. coli isolates and the MIC90 for isepamicin was two-fold lower than that of amikacin. Isepamicin retained its inhibitory activity against 95% of amikacin resistant and 97% of gentamicin resistant ESBL expressing E. coli isolates. There were 31% of amikacin-resistant and 22% of gentamicin-resistant, carbapenemase-expressing E. coli isolates were susceptible to isepamicin. Conclusion: The findings suggest that isepamicin may be useful for treating community acquired urinary tract infection as monotherapy and systemic ESBL-E. coli infection as combination therapy, due to its minimal nephrotoxicity and ototoxicity, compared to other aminoglycosides.